Fairy-tales "About Czar-Saltan" and "About Dead Czarevna" recorded anew - Mitropolskaja, N. (Literatūra, 1969)
A scientific and objective explanation of many folklore problems, including one of the most complex problems – the present state of the traditional Russian fairy-tale – can be given only if not limiting oneself to fairy-tales recorded in the territory of the U.S.S.R., but expanding the geographic volume of the material under investigation at the expense of the variants existing in other national republics.The folklore material gathered in the places of the Lithuanian S.S.R. inhabited by Russian natives, especially in the districts of Zarasai, Ignalina, Anykščiai, reveals many interesting facts about the development of fairy-tales in different bilingual surroundings.The state of the Russian folklore in the territory of a national republic makes it possible to maintain and develop interesting motifs and details of fairy-tales. The fairy-tales ("About Czar-Saltan" and "About Dead Czarevna") published in the appendix of the present article were chosen from the wide repertoire of magic tales recorded from local Russian natives. They are interesting as "pre-Pushkin" plots known in oral variants comparatively little, and as new records of fairy-tales in districts earlier not investigated.
Keywords: -